Effectiveness of Combined Unplugged and Block-Based Programming Approaches on Computational Thinking Skills and Programming Attitudes Across Gender - Badruliman, Batni (Unimas Publisher, 2024)
This study addresses the challenge of effectively developing computational thinking (CT) skills and fostering positive attitudes towards programming among secondary students in fully boarding schools in Kedah, Malaysia. The primary objective is to evaluate the impact of integrating Unplugged Activities (UA) with Block-Based Programming (BBP) (UA+BBP) compared to using BBP alone. The proposed solution combines tactile, hands-on activities with digital programming tools to create a more engaging and comprehensive learning experience. Using a quasi-experimental design with mixed-methods analysis, the study involved two groups: one using only BBP and the other using UA+BBP. Quantitative analysis, including two-way ANCOVA and Welch’s ANOVA, was used to assess the effects of teaching methods and gender on CT skills and programming attitudes. Results showed that while both groups improved in CT skills, there were no statistically significant differences in post-test scores between the two teaching methods. Gender did not significantly impact CT skill development. However, the UA+BBP group exhibited significantly higher attitudes towards programming compared to the BBP-only group (mean difference = 0.65741, p < 0.001). Additionally, the integrated approach balanced gender differences in attitudes, unlike the BBP-only group where males scored significantly higher than females. Qualitative data from student interviews provided deeper insights, revealing that fun and challenging UA+BBP activities enhanced their understanding of CT and made programming more accessible and enjoyable. The findings suggest that integrating unplugged activities with BBP not only enriches students’ learning experiences but also cultivates a more positive and inclusive attitude towards programming. This study underscores the potential of blended teaching strategies in advancing CT education in secondary schools.